Determinan Partisipasi Angkatan Kerja Perempuan dalam Pengentasan Kemiskinan Rumah Tangga di Indonesia - Mulya Sari, Gusti; Artha, Dwirani Puspa (Universitas Negeri Padang, 2025)
This study aims to identify and examine the impact of female labor force participation on household poverty alleviation in Indonesia. The research utilizes secondary data from the 2020 National Socio-Economic Survey (SUSENAS) conducted by Statistics Indonesia. The variables in this study are categorized into three groups: the dependent variable, which is household poverty status; the independent variable, which is female labor force participation; and control variables, including the education level of the household head, number of household members, gender of the household head, marital status, divorce status, age of the household head, and access to credit. The analytical method employed is logistic regression using 2020 cross-sectional data. The results indicate that female labor force participation has a negative and significant effect on household poverty status, implying that it contributes to the reduction of household poverty in Indonesia.